Thermal characterization of bacterial cellulose-phosphate composite membranes - Barud, H. S.; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Martines, M. A. U.; Dexpert-Ghys, J.; Marques, Rodrigo Fernando Costa [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Springer, 2007)
Cellulose-phosphate composite membranes have been prepared from bacterial cellulose membranes ( BC) and sodium polyphosphate solution. The structure and thermal behavior of the new composites were evaluated by X-ray diffraction (XRD), P-31-nuclear magnetic resonance (NMR), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermogravimetry (TG) and thermomechanical analysis (TMA). From XRD analyses the I alpha and I beta cellulose crystalline phases were identified together with crystalline sodium phosphate that covers the cellulose microfibrils as revealed by SEM. P-31 NMR spectra show peaks assigned to Q(0) and Q(1) phosphate structures to be compared to the Q(2) units that characterize the precursor polyphosphate. Glass transition temperature, T-g, obtained from TMA curves and thermal stability obtained from TG and DSC measurements, were observed to be dependent on the phosphate content.
Keywords: bacterial cellulose; cellulose-phosphate composites; sodium polyphosphate